Toothpick ingestion causing rectum perforation - Çapkınoğlu, Emir; Özsay, Oğuzhan; Örsel, Atilla; Karaisli, Serkan (Turkish Journal of Gastroenterology, 2017)
Abstract Cite this article as: Çapkınoğlu E, Özsay O, Örsel A, Karaisli S. Toothpick ingestion causing rectum perforation. Turk J Gastroenterol 2017; 28: 540-1.